How Strong are Fiscal Multipliers in the GCC? - Espinoza, Raphael; Senhadji, Abdelhak (Washington, D.C. : International Monetary Fund, 2011)
The effectiveness of fiscal policy in smoothing the impact of shocks depends critically on the size of fiscal multipliers. This is particularly relevant for the GCC countries given the need for fiscal policy to cushion the economy from large terms of trade shocks in the absence of an independent monetary policy and where fiscal multipliers could be weak dues to substantial leakages through remittances and imports. The paper provides estimates of the size of fiscal multipliers using a variety of models. The focus is on government spending since tax revenues are small. The long-run multiplier estimates vary in the 0.3-0.7 range for current expenditure and 0.6-1.1 for capital spending, depending on the particular specification and estimation method chosen. These estimates fall within the range of fiscal multiplier estimates in the literature for non-oil emerging markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet